2002
DOI: 10.1053/ejvs.2002.1721
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Catecholamines in Buerger's Disease: Effects of Cigarette Smoking and Surgical Sympathectomy

Abstract: in Buerger's disease there is an impairment of sympathoadrenal function with an altered peripheral adrenergic response to cigarette smoking. Patients submitted to sympathectomy have high pAD, but this benefit is reversed after smoking. This might be clinically relevant given the association between cigarette smoking and the manifestations of Buerger's disease and the controversy on the effectiveness of sympathectomy in the management of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Our results, however, showed that P. gingivalis induces intimal hyperplasia without host hypercholesterolemia. Although the distinct molecular mechanisms involved in this discrepancy should be analyzed further in detail, other reports have noted that Burger’s disease, an occlusive vascular disease, occurs in individuals infected with P. gingivalis , despite the absence of cholesterol elevation in plasma (32–34), which supports the present findings. Another intriguing finding is that P. gingivalis in the bloodstream fails to gain access to the vessel wall across the uninjured endothelial layer.…”
Section: Discussionsupporting
confidence: 89%
“…Our results, however, showed that P. gingivalis induces intimal hyperplasia without host hypercholesterolemia. Although the distinct molecular mechanisms involved in this discrepancy should be analyzed further in detail, other reports have noted that Burger’s disease, an occlusive vascular disease, occurs in individuals infected with P. gingivalis , despite the absence of cholesterol elevation in plasma (32–34), which supports the present findings. Another intriguing finding is that P. gingivalis in the bloodstream fails to gain access to the vessel wall across the uninjured endothelial layer.…”
Section: Discussionsupporting
confidence: 89%
“…These cases might be triggered by cold, frostbite, traumatism of extremities or even abuse of sympathicomimetic drugs 1. The use of drugs such as cocaine, cannabis and amphetamines may mimic TAO, showing a similar arteriographic pattern 10 11…”
Section: Discussionmentioning
confidence: 99%
“…The proliferative smooth muscle cells migrate into the intima and stimulate cell growth, resulting in the development of an aortic intimal hyperplasia that is unrelated to cholesterol deposition. A similar mechanism may explain why Buerger’s disease often occurs in subjects with P. gingivalis infection but without elevated plasma cholesterol levels (64, 79, 84). Smoking is the most important risk factor for Buerger’s disease, perhaps because reactive oxygen species generated in the blood cause injury to endothelial cells.…”
Section: P Gingivalis‐induced Novel Smooth Muscle Cell‐mediated But mentioning
confidence: 99%
“…Nevertheless, in other types of vascular disease such as BuergerÕs disease, the plasma cholesterol level is not related to disease onset (64,79,84). Buer-gerÕs disease, an occlusive vascular disease, comprises recurring inflammation and thrombosis of the arteries and veins of the hands and feet.…”
mentioning
confidence: 99%